ERF5 and ERF6 Play Redundant Roles as Positive Regulators of JA/Et-Mediated Defense against Botrytis cinerea in Arabidopsis - Moffat, Caroline; Ingle, R.; Wathugala, D.; Saunders, N.; Knight, H.; Knight, M. (Public Library of Science, 2012)
The ethylene response factor (ERF) family in Arabidopsis thaliana comprises 122 members in 12 groups, yet the biological functions of the majority remain unknown. Of the group IX ERFs, the IXc subgroup has been studied the most, and includes ERF1, ERF14 and ORA59, which play roles in plant innate immunity. Here we investigate the biological functions of two members of the less studied IXb subgroup: ERF5 and ERF6. In order to identify potential targets of these transcription factors, microarray analyses were performed on plants constitutively expressing either ERF5 or ERF6. Expression of defense genes, JA/Et-responsive genes and genes containing the GCC box promoter motif were significantly upregulated in both ERF5 and ERF6 transgenic plants, suggesting that ERF5 and ERF6 may act as positive regulators of JA-mediated defense and potentially overlap in their function. Since defense against necrotrophic pathogens is generally mediated through JA/Et-signalling, resistance against the fungal necrotroph Botrytis cinerea was examined. Constitutive expression of ERF5 or ERF6 resulted in significantly increased resistance. Although no significant difference in susceptibility to B. cinerea was observed in either erf5 or erf6 mutants, the erf5 erf6 double mutant showed a significant increase in susceptibility, which was likely due to compromised JA-mediated gene expression, since JA-induced gene expression was reduced in the double mutant.Taken together these data suggest that ERF5 and ERF6 play positive but redundant roles in defense against B. cinerea. Since mutual antagonism between JA/Et and salicylic acid (SA) signalling is well known, the UV-C inducibility of an SA-inducible gene, PR-1, was examined. Reduced inducibilty in both ERF5 and ERF6 constitutive overexepressors was consistent with suppression of SA-mediated signalling, as was an increased susceptibility to avirulent Pseudomonas syringae. These data suggest that ERF5 and ERF6 may also play a role in the antagonistic crosstalk between the JA/Et and SA signalling pathways.